2008
DOI: 10.1007/s11249-008-9330-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence on Boundary Friction of the Permeability of Sintered Bronze

Abstract: Components made of sintered bronze are often used in tribological systems. Examples of applications are self lubricated bearings, wet clutches and brakes and synchromesh components for manual gearboxes. The bronze material in these applications is often porous and permeable. However, the required level of permeability i.e., the ability for a fluid to flow inside the material varies widely for different applications. This implies the need to investigate if the permeability can influence the properties of a trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A characteristic of sintered materials is their porosity. The pores in the material can act as reservoirs for the lubricant and capillary forces keep the fluid in place [14]. An image of the sintered bronze surface taken with a scanning electron microscope (SEM) can be seen in Fig.…”
Section: Materials and Lubricantsmentioning
confidence: 99%
“…A characteristic of sintered materials is their porosity. The pores in the material can act as reservoirs for the lubricant and capillary forces keep the fluid in place [14]. An image of the sintered bronze surface taken with a scanning electron microscope (SEM) can be seen in Fig.…”
Section: Materials and Lubricantsmentioning
confidence: 99%
“…Tin bronze has excellent corrosion resistance, fatigue resistance, wear resistance as well as high strength [1][2][3], and it is usually cladded on the thin steel sheet in order to form the tin bronze/steel bimetallic sheet, which can be used to make various kinds of bearings and bushes [4][5][6]. Tin bronze cladding layer prepared by traditional powder sintering process has problems such as high porosity and coarse grain [7,8]. Therefore, there is a need to study a new method for fabricating tin bronze layer on thin steel sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Fei et al [4] studied the influence of the composition of friction materials on the dynamic friction torque during engagement. Marklund et al [5] investigated the effect of the permeability on the temperature during engagement. It was found that the permeability can affect engagement time, temperature of the clutch and boundary lubrication friction coefficient.…”
Section: Introductionmentioning
confidence: 99%